Ligand-Independent EGFR Activation by Anchorage-Stimulated Src Promotes Cancer Cell Proliferation and Cetuximab Resistance via ErbB3 Phosphorylation - Masami Nozaki (Cancers, 2019)
Activation of the epidermal growth factor receptor (EGFR) pathway plays an important role in the progression of cancer and is associated with a poor prognosis in patients. The monoclonal antibody cetuximab, which displays EGFR extracellular domain-specific binding, has proven effective in the treatment of locally advanced disease and relapsed/metastatic disease. However, the effects of cetuximab are weaker than those of EGFR tyrosine kinase inhibitors (TKIs). This study investigates differences in the effects on cell growth of cetuximab and EGFR TKI AG1478 at the molecular level using oral squamous cell carcinoma (OSCC) cell lines. First, we found that there were EGFR-inhibitor-sensitive (EIS) and EGFR-inhibitor-resistant cell lines. The EIS cell lines expressed not only EGFR but also ErbB3, and both were clearly phosphorylated. The levels of phosphorylated ErbB3 were unaffected by cetuximab but were reduced by AG1478. EGFR ligand treatment increased the levels of phosphorylated EGFR but not phosphorylated ErbB3. Moreover, when EIS cell lines that were only capable of anchorage-dependent growth were grown in suspension, cell growth was suppressed and the levels of phosphorylated focal adhesion kinase (FAK), Src, and ErbB3 were significantly reduced. The levels of phosphorylated ErbB3 were unaffected by the FAK inhibitor PF573228, but were reduced by Src inhibition. Finally, combining cetuximab and a Src inhibitor produced an additive effect on the inhibition of EIS cell line growth.